Measurement of Hip Range of Flexion-Extension and Straight-leg Raising - Elson, R. A. (Springer-Verlag, 2008)
We believe there is a degree of inaccuracy in the usual methods of evaluation of range at the hip in the sagittal plane, ie, flexion-extension. We describe a simple method of measuring more accurately the range of hip flexion-extension, presuming such ranges of motion should relate to the anatomic position of the pelvis. We used this technique for the measurement of flexion and extension of the left hip in a cohort of 200 healthy individuals; we found a wide range of both flexion (80°–140°) and extension (5°–40°). Especially with respect to extension, we believe more conventional methods underestimate the ranges of motion. As a corollary to this study, we suggest some reappraisal of the straight-leg–raising test by which pain from nerve root tension can be distinguished from a source of pain arising locally in intervertebral joints for mechanical reasons or from the hip itself. We recommend the method described as being useful in the consulting office.